Contemporary Malaysia and Challenges of the Times - Abdul Rahman Embong, (Kajian Malaysia, 2015)
Of late much has been debated in both the academic and the public spheres on several key challenges faced by contemporary Malaysia. A number of research and writings have been produced discussing the subject. In this short piece, I would like to address two things with regard to the theme, namely, the challenges of the times from the perspective of social science; and second, to comment on a recent edited volume entitled Routledge Handbook of Contemporary Malaysia (edited by Meredith Weiss) which is part of the scholarly debate on the various dimensions of this country.